A educação ambiental na microrregião do Caparaó (ES): estudo das concepções pedagógicas de professores dos municípios de Alegre e Guaçuí - Paula, Viviane Tavares de (2022)
The present research had as its object of study the analysis of the pedagogical conceptions of teachers regarding environmental education, claiming as a means of investigation the man-nature relationship. To understand the conceptions that teachers present, it was necessary to investigate how environmental education was inserted in the pedagogical field and how social and environmental issues are addressed by teachers. The study was based on the analysis of the characteristics and principles that emerge from the discourses of teachers regarding their environmental pedagogical conception. It was a proposal for a qualitative study that uses a semistructured interview as a data collection instrument. The individuals of investigation were the professors of the disciplines of Chemistry, Biology, History and Geography who work in the municipalities of Alegre and Guaçuí, located in the Microregion of Caparaó. The study of this material, in turn, took place through the analysis of these discourses, using the Bakhtinian perspective of language as a theoretical-methodological framework. By understanding the pedagogical conceptions of environmental education as ideological discourses, we organized the analysis of teachers discursive statements in the light of three political-pedagogical perspectives (or macro-trends), which are called the conservationist environmental education, the pragmatic environmental education and the critical environmental education. We can say, roughly, that the reproduction of the ecological discourse and the eco-capitalist discourse by the teachers reproduces an uncritical conception of environmental education, which was fundamentally reduced as a behavioral and individual values, which does not incorporate into its reflection the social relations that organize the production and the way of life in the capitalist system, according to which that happens the relationship between man and nature in the contemporary world. Thus, the discourses that predominate in environmental education act by imposing on the public the gaze of the hegemonic actors of this society, which, by the way, is an expression of interests that are hegemonic in the capitalist system. On the other hand, the vision that seeks to problematize the analysis of environmental education from the critique of the current way of life, by turning back to the transformation or even the rupture of this model of society, imposes itself as a counter-hegemonic tendency. In this way, the research aimed to contribute to the discussions of the theme in the Microregion of Caparaó, seeking to highlight its controversies in the school environment and the importance of working the debate on the human-nature relationship in a way connected with our immediate reality.